Bioavailability of vitamin C from kiwifruit in non-smoking males: determination of ‘healthy’ and ‘optimal’ intakes - Anitra C. Carr; Juliet M. Pullar; Stephanie Moran; Margreet C. M. Vissers (Journal of Nutritional Science, 2012)
Vitamin C is an essential nutrient in humans and must be obtained through the diet. The aim of this study was to determine vitamin C uptake in healthy volunteers after consuming kiwifruit (Actinidia chinensis var. Hort. 16A), and to determine the amount of fruit required to raise plasma vitamin C to ‘healthy’ (i.e. >50 µmol/l) and ‘optimal’ or saturating levels (i.e. >70 µmol/l). Leucocyte and urinary vitamin C levels were also determined. A total of fifteen male university students with below average levels of plasma vitamin C were selected for the study. Weekly fasting blood samples were obtained for a 4-week lead-in period and following supplementation with, sequentially, half, one, two and three Gold kiwifruit per d for 4–6 weeks each, followed by a final 4-week washout period. The results showed that addition of as little as half a kiwifruit per d resulted in a significant increase in plasma vitamin C. However, one kiwifruit per d was required to reach what is considered healthy levels. Increasing the dose of kiwifruit to two per d resulted in further increases in plasma vitamin C levels as well as increased urinary output of the vitamin, indicating that plasma levels were saturating at this dosage. Dividing the participants into high and low vitamin C groups based on their baseline plasma and leucocyte vitamin C levels demonstrated that it is critical to obtain a study population with low initial levels of the vitamin in order to ascertain a consistent effect of supplementation.